A STUDY ON IMPACT OF NURSING STAFF TURNOVER ON HOSPITAL EFFICIENCY AT A TRUST-BASED HOSPITAL, VADODARA (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Very limited studies of nurse turnover have been  conducted in spite of rising rates of turnover,  especially in private and trust-based hospitals.  The object of this the study is to conduct an  empirical study of the causes and consequences  of nursing turnover in a trust-based hospital.  In this study, essential information (Primary  data) was gathered to search the exact reasons  behind turnover and its subsequent outcome;  notwithstanding that the researcher also  accumulated secondary data to ascertain the  precise causes of turnover. To investigate the  causes and its subsequent results of nurse  turnover, all hypotheses are tested by the  statistical (kruskal Wallis test) process. Nurse, Turnover, Workload, Job-Satisfaction,  Conflict, Workflow, Increased-Cost, Stress and  Patient- Flow:
Keywords: Nurse; Workload; Conflict; Increased-Cost; Stress and Patient- Flow